Mobilizing Parents at Home and at School : An Experiment on Primary Education in Angola - Di Maro, Vincenzo; Leeffers, Stefan; Serra, Danila; Vicente, Pedro C. (World Bank, Washington, DC, 2021)
How should parents be mobilized for education in Africa This study implemented a large-scale field experiment in Angolan primary schools, including three treatments: an information campaign at home, simple parents’ meetings at school, and the combination of both. The measures of parental mobilization include beneficial practices at home, contacts with teachers, and participation in school institutions. The findings show that the information increased parents’ involvement at home but had no impact on engagement at school, while the meetings had the opposite effects. After mobilizing parents, only the combined treatment improved management practices and facilities in schools, teachers’ attitudes, and parents’ satisfaction.